Teaching children online a conversation-based approach - Meskill, Carla; Anthony, Natasha (MM textbooks, 2019)
"What does best practice in online education look like? How can educators make use of the affordances offered by online environments to bring out the best in the children they teach? These questions are answered in this new textbook, written with experienced teachers, novice educators and teacher educators in mind"--Provided by publisher.